Factors that would guarantee a better development of future French language teaching projects, based on previous experiences of programs Carried out in the metropolitan area of San Salvador, since the year 1990 - Fuentes Muñoz, Dina Florisel; Gómez Landaverde, Katherine Lizeth; Siciliano Pérez, Marlene Carolina (2024)
Being French a language with an important impact in business, education and job opportunities, it has become a necessity, as English does, to include it in schools’ programs as projects that can be developed with an improvement every year they are implemented. That is the importance in which this research will be focused. With the analysis of the projects that have been implemented in the Public Schools of the Metropolitan Area of San Salvador since the year 1990, it will be easier to identify the factors that would guarantee a better development of future programs carried out in schools, looking forwards to benefiting not only students but also all the involved ones in the process. In order to accomplish the goals of this research project, the researchers will be using a Qualitative-Descriptive method to observe and show the experiences coming from the previous French Language Teaching programs and projects, through interviews, questionnaires, and a checklist that will provide the results of the processes, the strengths, and the weaknesses of each program.